Nucleus Disc Replacement: Design and Material Selection FEA Analysis - Amparo Vanaclocha; Vicente Vanaclocha; Carlos M. Atienza; Pablo Clavel; Pablo Jorda-Gomez; Carlos Barrios; Nieves Saiz-Sapena; Leyre Vanaclocha (Advances in Materials Science and Engineering)
Study Design. We selected the materials and implant design and performed Finite Element Analysis (FEA) studies. Background. Nucleus disc replacements, implanted since 1960, have undergone continuous evolution in materials and designs, but subsidence, extrusion, and in vivo degradation limit widespread use. Aim. The aim of this study is to create a new nucleus disc replacement that avoids the abovementioned drawbacks. Material and Methods. We created eighteen designs with varied materials and analyzed them with FEA in compression and shear tests in a lumbar spine model programmed in Ansys Parametric Design Language. Results. Bionate® 80A had the closest mechanical characteristics to the intact disc nucleus. Monobloc designs bore physiological stresses correctly but suffered significant deformations with permanent damage during surgical insertion through the annulus opening. In addition, sandwich designs were too rigid and had an unreliable curing process. Therefore, we chose an oval doughnut-like 5 mm wall monobloc Bionate® 80A nucleus replacement. It minimized implant stress in loading, distributed loads uniformly, and tolerated lateral compression during implantation. Conclusions. Out of the eighteen designs we analyzed with FEA, we found that the monobloc oval doughnut-like Bionate 80A nucleus replacement reproduced best the biomechanics of the natural disc nucleus and had the lowest subsidence risk as it transmits the load to the ring apophysis. Furthermore, implanting it through the annulotomy required to perform a lumbar microdiscectomy should be possible due to its elasticity. Furthermore, due to its elasticity implanting it through the average annulotomy required to perform a lumbar microdiscectomy should be possible.